Pengaruh Penambahan Media Karbon Aktif dan Zeolit Terhadap Peningkatan Kinerja Tray Aerator Pada Air Sumur - Septi Ika Nurfadila; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In the well water of Sengon Village, the levels of Fe (iron) and Mn (manganese) exceed the established quality standards of 0.743 mg/L and 1.60 mg/L respectively. One of the treatment solutions to reduce these contaminant levels is the aeration method of the aeration tray with the addition of media. The aeration method works by bringing water into contact with oxygen. The aim of this study is to determine the optimum performance of tray aerators by comparing the addition of activated carbon, zeolite or mixed media. Each media has an influence on the measurement results of pollutant levels in units of percent removal. The parameter with the highest weight is the one that most influences the effectiveness in removing Fe and Mn. The values of the parameter variations were then analysed and Anova Two Way statistical test was performed. The results showed that the most optimal reduction of Fe levels was achieved by aeration with activated carbon media with an aeration time of 150 minutes with a percentage removal of 96.67% and a level of 0.0234 mg/L. To reduce Mn levels, the most optimal aeration with addition of zeolite media with an aeration time of 150 minutes with a percent removal of 99.08% and levels <0.0145 mg/L. And to increase DO levels, the most optimal is aeration with the addition of activated carbon media with an aeration time of 150 minutes and a final DO value of 6 mg/L.